The implementation of unmanned aerial vehicle (UAV) for slope mapping - M. F., Zolkepli; Mohd Fakhrurrazi, Ishak; F. N. A., Zolfan; N. S., Yusoff; S., Daud; N. S., M. Zin (Penerbit Universiti Malaysia Pahang, 2023)
This paper discusses the applications of unmanned aerial vehicle (UAV) for slope mapping and its important parameters including perimeter, area and volume of certain selected areas at Perumahan Taman Gambang Damai in Kuantan Pahang. This study also focused on determining the potential slope hazard based on slope angle. Modern UAV able to take high quality image which essential for the effectiveness and nature of normal mapping output such as Digital Elevation Model (DEM) and Digital Orthophoto. This photo captured by the UAV will later transfer to Agisoft to generate full map of study area. With the help of Global Mapper, the measurement (perimeter, area and volume) of selected study areas can be determined easily and considered as the main interest in this study. In addition, another outcome of this study is, this modern method of mapping helps researchers and engineers to study the possibility of slope hazard based on their respective slope angle (according to slope classes). In conclusion, modern technology of UAV proves to be very effective for mapping in geotechnical engineering. Slope mapping help researchers and engineers to obtain slope measurement within short period of time compare to previous traditional method.